EFFECT OF MENTAL HEALTH PROBLEMS ON PRIMARY SCHOOL PUPILS: COUNSELLING IMPLICATIONS - Mommoh, Grace O. (Sokoto Educational Review, 2011)
This paper shows that the mental health of children is very important. This is not only because they are the future leaders but also due to the fact that good mental health brings about progress and achievement. The paper also shows that children can have mental health problems if care is not taken. As a result of this, the paper looked into the devastating effect of mental health problems, the causes, how to identify the problems and the counselling intervention that can be employed in solving some of the problems. Relevant recommendations were advanced.